Chloroplast Phylogenomics Indicates that Ginkgo biloba Is Sister to Cycads - Wu, Chung-Shien (Oxford University Press, 2013)
Molecular phylogenetic studies have not yet reached a consensus on the placement of Ginkgoales, which is represented by the only living species, Ginkgo biloba (common name: ginkgo). At least six discrepant placements of ginkgo have been proposed. This study aimed to use the chloroplast phylogenomic approach to examine possible factors that lead to such disagreeing placements. We found the sequence types used in the analyses as the most critical factor in the conflicting placements of ginkgo. In addition, the placement of ginkgo varied in the trees inferred from nucleotide (NU) sequences, which notably depended on breadth of taxon sampling, tree-building methods, codon positions, positions of Gnetopsida (common name: gnetophytes), and including or excluding gnetophytes in data sets. In contrast, the trees inferred from amino acid (AA) sequences congruently supported the monophyly of a ginkgo and Cycadales (common name: cycads) clade, regardless of which factors were examined. Our site-stripping analysis further revealed that the high substitution saturation of NU sequences mainly derived from the third codon positions and contributed to the variable placements of ginkgo. In summary, the factors we surveyed did not affect results inferred from analyses of AA sequences. Congruent topologies in our AA trees give more confidence in supporting the ginkgo–cycad sister-group hypothesis.